2021
DOI: 10.1155/2021/5545620
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Relationship between Drink Intake and Periodontitis Using KoGES Data

Abstract: It was hypothesized that periodontal diseases could be influenced by nutrition and food types. However, the role of nutritional factors in the risk of periodontal disease has not been clearly elucidated. This study was aimed at investigating the relationship between coffee, green tea, or soft drink intake and periodontitis. This prospective cohort study used epidemiological data from 2004 to 2016 from the Korean Genome and Epidemiology Study. Among 173,209 participants, 9,933 with periodontitis and 124,922 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 48 publications
(59 reference statements)
0
19
0
Order By: Relevance
“…One study used data from dental longitudinal studies, one study used data from Genome and Epidemiology Study, one used general population, and one other study selected chronic periodontitis patients who had received initial treatment as the participants of the study. All of the human studies used questionnaire to assess the dose of daily coffee consumption (all six studies), [8][9][10][11][12][13] one study also used Cornell Medical Index (CMI) to gain coffee consumption in addition to questionnaire. 9 Two studies admitted that validity and reliability test of the questionnaire were not performed sufficiently, therefore, further research is required.…”
Section: Methodological Qualitymentioning
confidence: 99%
See 3 more Smart Citations
“…One study used data from dental longitudinal studies, one study used data from Genome and Epidemiology Study, one used general population, and one other study selected chronic periodontitis patients who had received initial treatment as the participants of the study. All of the human studies used questionnaire to assess the dose of daily coffee consumption (all six studies), [8][9][10][11][12][13] one study also used Cornell Medical Index (CMI) to gain coffee consumption in addition to questionnaire. 9 Two studies admitted that validity and reliability test of the questionnaire were not performed sufficiently, therefore, further research is required.…”
Section: Methodological Qualitymentioning
confidence: 99%
“…13 Aside from periodontal health, caries measurement using DMFT index was also performed. 13 In terms of bias, some studies also observed several confounding factors, such as Body Mass Index (BMI) 9,11,13 and other nutritional intake, 11 smoking and alcohol habit, 9,[11][12][13] medical history such as diabetes, 8,9,12,13 cholesterol level 8 and coronary heart diseases, 12,13 blood sample analysis, 8 and other socio-demographic factors. 10,12…”
Section: Methodological Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…Chlorogenic acid from coffee demonstrated a direct inhibitory effect on Porphyromonas gingivalis, a major pathogen key-player of periodontitis [16] and can indirectly affect the bioavailability of other nutrients and thereby modulate periodontal disease prevalence [18]. A few studies suggest an association between coffee intake and periodontitis [19][20][21][22][23]. The US Department of Veterans Affairs Dental Study included 1,231 participants and reported no harmful but rather a beneficial effect of coffee on periodontal health [22].…”
Section: Introductionmentioning
confidence: 99%